ANALISIS KINERJA SISTEM KEUANGAN SYARIAH TERHADAP PERTUMBUHAN EKONOMI INDONESIA - Khoirul Zadid Taqwa; Raditya Sukmana (Universitas Airlangga, 2018)
This research is aimed to examinethe contribution of Islamic finance performacesystem especially intermediation function to economic growth in Indonesia during 2003:Q1- 2015:Q4.Objects of this research areIslamic bank and Jakarta Islamic stock index (JII) as representing Indonesia Islamic financial system. This research only focuses on financing of Islamic financial Instutions to foster Indonesia economic growth.Focusing on the post-1997 and 2008 economic turmoil, the paper relies on Autoregressive Distributed Lag (ARDL) approach to examine the research. This research shows that Indonesia Islamic finance performance system can foster Indonesia economic growth during 2003-2015. Besides Indonesia Islamic finance performance system has significant role to promote economic growth in long term because it can eradicate financial specualtion.Hence IndonesiaIslamic finance performance system in the future should be supported by goverment to expand Islamic finance market share REFERENCESAbduh, MuhamaddanMohdAzmi Omar. 2012. Islamic banking and economic growth: the Indonesian Experience. International Journal of Islamic and Middle Eastern Finance and Management. Vol. 5 No. 1, 2012 pp 35-47. DOI 10.1108/17538391211216811Ajija, Shochrul R dkk. 2011. Cara cerdas menguasai EViews. SalembaEmpat. JakartaAzam, Muhamad, et al. 2016. Stock Market Development and Economic Growth: Evidence from Asia-4 Countries. International Journal of Economics and Financial Issues. ISSN: 2146-4138. http: www.econjournals.comBadan Pusat StatistikaBudiono. 2016. Ekonomi Indonesia dalam Lintasan Sejarah. Bandung-MizanEkananda, Mahyus. 2016. Analisis Ekonometrika Time Series. Edisi Kedua. Jakarta. Mitra Wacana Media.Hamidi, M. Luthfi. 2012. The Crisis. Jakarta. RepublikaHossain, Akhand Akhtar. 2016. Inflanatory Shocks and Real Output growth in nine Muslim-majority countries: Implication for Islamic banking and Finance. Journal of Asian Economics No 45, pp. 56-73. DOI 10.1016/j.asieco.2016.06.004Huda, Nuruldan Mohammad Heykal. 2010. Lembaga Keuangan Islam: Tinjauan Teoretis dan Praktis. Jakarta: KencanaKajian Stabilitas Keuangan, Bank Indonesia 2014Karim, Adiwarman A. 2014.Bank Islam: Analaisis Fiqih dan Keuangan. Edisi 5. Jakarta: PT Raja Grafindo JakartaKassim, Salina. 2016. Islamic Finance and Economic Growth: The Malaysian Experience. Global Finance Journal No 30. Pp 66-76. DOI 10.1016/j.gfj.2015.11.007Levine, Ross. 1997. Financial Development of Economic Growth: Views and Agenda. Journal of Economic Literature, Vol. 35, hal 688-726Levine, Ross dan Sara Zervos. 1996. Stock Market Development and Long run growth. The World Bank Economic Review Vol 10 No 2Mankiw, N .gregory. 2007. Makroekonomi Edisi 6. Jakarta. ErlanggaMiskhin, F.S. 2006. The Economics of Money, Banking and Financial Markets, Seven Edition Update. Pearson, Addison WisleyState of the Global Economy Report 2013-2014, Thomson ReutersState of the Global Economy Report 2014-2015, Thomson ReutersState of the Global Economy Report 2015-2016, Thomson ReutersTamura, Robert, Kevin M Murphy, dan Gary S. Becker. 1994. Human Capital, Fertility, and Economic Growth. National Bureau of Economic Research. The University of Chicago. DOI 10.3386/w3414Todaro, Michael p dan Stephen C Smith. 2013. Pembangunan Ekonomi Edisi Kesebelas. Jilid satu. Jakarta-ErlanggaSholihin, Ahmad Ifham. 2010. Buku Pintar Ekonomi Syariah. Jakarta: Gramedia Pustaka UtamaSimorangkir, Iskandar. 2014. Pengatar Kebanksentralan: Teori dan Praktik di Indonesia. Jakarta: Raja Grafindo PersadaSukirno, Sadono. 2015. Teori Pengantar Makroekonomi. Jakarta: PT. Raja GrafindoWahyudi, Imam dan Gandhi Anwar Sani. 2014. Interdependence between Islamic capital market and money market: Evidence from Indonesia. Borsa Istanbul Review Journal 14. DOI 10.1016/j.bir.2013.11.001